KEMAMPUAN MEMBACA TEKS EKSPOSISI SISWAKELAS X MA MUHAMMADIYAH PEKANBARU - Mona Lisa; Mangatur Sinaga; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study examines the ability to reading the text of the exposition of student of class X MA Muhammadiyah Pekanbaru. The purpose of this study is to know and describe the level of ability to read exposition of the text of student of class X MA Muhammadiyah pekanbaru and describe wheater there is difference in reading ability of exposition student of class X MA Muhammadiyah Pekanbaru in grup of sample and gander. This study has a population of 26 and sample of 24. The results of research when tested by using t test one sampel is the ability to read exposition text is not aqual to value of comparison. The comparativevalue applied is 14 whereas the result obtained is 12,42. The ability to read the text of the exposition of class X MA Muhammadiyah Pekanbaruquite low, in other words the hypothesis is rejected. Then tested using a two-way anova. The result is that there is difference of reading ability of exposition text of class X MA Muhammadiyah Pekanbaru student in sampel group and gander. Based on result of research, it can be seen that students reading ability is very low because student do not understand the content in the tructure of the text of the exposition, the main ideas in the general statement, the main idea in argumentation, the main ideas in the reaffirming of opinions, the idea of exposision in the argumentasi, explanatory ideas in reaffirming opinions, conclusion and mandates. Then student are less serious in working on the questions given.Keywords: Ability, Reading, Exposition Text, Student